The 100 most-cited articles in hypothermic brain protection journals: a bibliometric and visualized analysis - Hu, Liren; Geli, Sirui; Long, Feiyu; Nie, Liang; Wu, Jiali; Zhou, Jun; Wang, Maohua; Chen, Yingxu (Frontiers in Neurology, 2024)
Introduction A bibliometric analysis is used to assess the impact of research in a particular field. However, a specialized bibliometric analysis focused on hypothermic brain protection has not yet been conducted. This study aimed to identify the 100 most-cited articles published in the field of hypothermic brain protection and analyze their bibliometric characteristics. Methods After screening articles from the Web of Science citation database, complete bibliographic records were imported into Python for data extraction. The following parameters were analyzed: title, author’s name and affiliation, country, publication year, publication date, first author, corresponding author, study design, language, number of citations, journal impact factors, keywords, Keywords Plus®, and research topic. Results The 100 articles were published between 1990 and 2016. The citation frequency for each publication ranged from 86 to 470. Among the 100 articles, 73 were original articles, 18 were review articles, 8 were clinical articles, and 1 was editorial material. These papers were published in 37 journals, with the Journal of Cerebral Blood Flow and Metabolism being the most prolific with 15 papers. Eighteen countries contributed to the 100 publications, 51 of which were from United States institutions. In addition, the keywords in the Sankey plot indicated that research in the field of hypothermic brain protection is growing deeper and overlapping with other disciplines. Discussion The results provide an overview of research on hypothermic brain protection, which may help researchers better understand classical research, historical developments, and new discoveries, as well as providing ideas for future research.